Drying kinetics and quality characteristics of Eucheuma cottonii seaweed in various drying methods. Issue 2 (26th December 2021) - Jamaluddin,; Yahya, Muhammad; Rauf, Reski Febyanti; Rivai, Andi Alamsyah
Abstract: This study aims to investigate the drying kinetics and the quality characteristics of Eucheuma cottonii seaweed, which was dried in tarpaulin, bamboo shelf, and solar dryer method. Drying rate, moisture content (MC), moisture ratio, effective moisture diffusivity, carrageenan content, gel strength, and color were analyzed. The results showed that the drying kinetics of E . cottonii were included in the falling‐rate period. Modified Midilli‐Kucuk model was selected to describe the drying kinetics of E . cottonii in all drying methods accurately. The solar dryer method produced dried seaweed with the lowest MC (12.066% db). The analysis of carrageenan content and gel strength showed that the tarpaulin method had higher results than other methods ( p < .05). The tarpaulin method had a higher effective moisture diffusivity but produced dried seaweed with a higher browning index if compared to other methods ( p < .05). The results of this study are expected to provide the theoretical basis for improving the quality of dried E . cottonii . Novelty impact statement: In this article, we identified the most suitable drying model for describing the drying kinetics of Eucheuma cottonii seaweed by drying method of tarpaulin, bamboo shelf, and solar dryer. We also reported differences in the quality characteristics of the dried seaweed produced from various drying methods used in this study. The findings of this study are expected to provide a theoretical basis for E . cottonii drying, allowing for process optimization and improved dried E . cottonii quality.